Maqāshid Sharia-Based Zakat Distribution Model: Zakat Distribution Program in National Zakat Agency DKI Jakarta - Mahmudah, Siti Nur; Aziz Alwa, Moh Abdul (Invest Journal of Sharia & Economic Law, 2022)
Based on Law Number 23 of 2011 concerning Zakat Management, which strengthens BAZNAS as an institution authorized to manage Zakat responsible for supervising zakat management based on Islamic law, mandate, benefit, justice, legal certainty, integration, and accountability, the purpose of this article is to explain how BAZNAS distributes Zakat in DKI Jakarta. The research method involves literature, including websites, books from the National Amil Zakat Agency, and articles on the studied topics. The National Amil Zakat Agency (BAZNAS) distributes economic empowerment, economic programs, and educational programs from the point of view of dharuriyat (faith, soul, descent, reason, and wealth), hajiyyat, and tahsiniyat (BAZNAS). Regarding Maqāshid Sharia, this paper concludes that the "Jak B Be Taqwa" program, the "Jak B Cerdas" program, the "Jak B Sehat" program, the "Jak B Hijau" program, and the "Jak B Berdaya" program implemented from 2019 to 2022 are a form of implementation of the Maqāshid Sharia -based zakat distribution model by BAZNAS in DKI Jakarta.